Strategies for Managing the Transport Sector to Achieve Sustainability The Experience of the Emirate of Abu Dhabi in Road Transport - Chenbi, Soureya; Benlakhdar, Said (The Arab Journal of Administration, 2021)
This research paper aims to clarify the concept of sustainable transport and highlight the most important strategies and policies for its development in accordance with the principles of sustainability, this sector that plays a fundamental role in development in its various dimensions at all regional and global levels, by facilitating exchanges, and remains the basis for large-scale infrastructure projects, that comes in support of rapid movement towards sustainable development. This led to the emergence of a new term, which is sustainable transport, which is considered a great warning to countries, especially developing countries, of the need to adopt effective strategies and policies. The study concluded with the presentation of the first Arab experience in the field of modernization and development of road transport activities embodied by the Emirate of Abu Dhabi as the most important emirate in the United Arab Emirates represented by the Abu Dhabi Department of Transport, which showed a clear commitment to present reports related to the application of principles and indicators of sustainability, in line with the vision Abu Dhabi 2030, and in pursuit of the International Public Transport Union’s Charter for Sustainable Development, in order to contribute to building a sustainable transport system and achieving an information infrastructure, by implementing a set of strategies that depend on advanced technological means.